THE IMPACT OF BANKING ON ECONOMIC GROWTH IN DEVELOPING COUNTRIES, EMPIRICAL EVIDENCE: SUB-SAHARA AFRICA - Nouri Alziyani, Amal (The journal of contemporary issues in business and government, 2024)
African countries are developing better economic and monetary reforms so as to gain the status of an emergent country over a certain period of time. This study seeks to shed light on the development of the banking sector in African countries, as well as studying the relationship between the development of the banking sector and the economic growth. This study was based on quantitative data available through the World Bank for The 32 African countries for the period 1993-2016. The results of the study showed a positive relationship between the granting of credit to the private sector by banks and the growth in GDP. The granting of credit encourages investment, reduces unemployment and increases per capita income. While there was a negative correlation between inflation and growth in GDP due to the inflation that causes investors to refrain from founding projects in inflationary countries because of the high risk of investment which affects GDP growth. There was also a negative correlation between trade balance and growth in GDP. Africa continent is mostly poor, developing and heavily dependent on exports, making the trade balance is not in its favor